A Competent Approach to Teaching Riddles in Primary Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyses about the methods of teaching the riddle genre in elementary grades. In the process of analysis, the peculiarities of this genre are also covered and its relationship with other sub-genres.